EXPANSION OF VISCERAL LEISHMANIASIS IN THE STATE OF RIO DE JANEIRO, BRAZIL: REPORT OF THE FIRST AUTOCHTHONOUS CASE IN THE MUNICIPALITY OF VOLTA REDONDA AND THE DIFFICULTY OF DIAGNOSIS - Sangenis, Luiz Henrique Conde; Lima, Sebastião Roberto de Almeida; Mello, Cíntia Xavier de; Cardoso, Daniela Trindade; Mello, Jurema Nunes; Santo, Maria Cristina Carvalho do Espírito; Tavares, Walter (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Visceral Leishmaniasis has been showing remarkable epidemiological changes in recent decades, with marked expansion and an emergence of cases in urban areas of the North, Southeast and Midwest regions of Brazil. The Kala-azar cases reported here, despite being very characteristic, presented a great difficulty of diagnosis, because the disease is not endemic in Volta Redonda. The child underwent two hospitalizations in different hospitals, but got the correct diagnosis only after 11 months of symptom onset. In this report we discuss the main differential diagnoses and call attention to the suspected symptoms of visceral leishmaniasis in patients with prolonged fever, hepatosplenomegaly and pancytopenia, even in areas not traditionally endemic for the disease.